Internalization Values of Anti-Bullying in Moral Education from Prophet’s Hadith (Arfannur: Journal of Islamic Education, 2024)
Moral education by instilling anti-bullying values is one solution to solve the problem of anti-bullying in the madrasah environment. This study aims to examine the hadiths of the Prophet Muhammad SAW that teach anti-bullying values as well as strategies and methods of internalizing anti-bullying values based on the Prophet's hadith in moral education in Madrasah Ibtidaiyah. This research is a literature review research. Data were taken from relevant literature sources such as books, scientific journals, and related articles. The data were analyzed using descriptive qualitative. The results showed that in the Islamic perspective, bullying includes various forms of harming others such as insulting, physically and psychologically hurting, and slander. Anti-bullying values in the hadith of Prophet Muhammad SAW are the prohibition of degrading behavior, protection from violence, respect for diversity, the obligation to defend the oppressed, and maintenance of the honor of fellow Muslims. Teachers can use expository learning, problem-based learning, project-based learning, and role-playing learning methods in the classroom learning process